Keberhasilan manajemen risiko bank syariah: Diversifikasi portofolio, instrumen keuangan syariah, dan penguatan pengawasan - Zaharani, Chanina Mumtaza (Maliki Interdisciplinary Journal, 2024)
This research aims to understand risk management carried out by Sharia Banks. The research method used is a literature study by collecting data from various related literature. The research results show that Sharia Bank has succeeded in implementing risk management effectively in managing credit, market, operational and sharia compliance risks. The strategies used include portfolio diversification, use of sharia financial instruments, and strengthening supervision and control systems. With good implementation, Sharia Bank has succeeded in reducing potential losses due to these risks and increasing operational stability in the Sharia banking industry. Apart from that, Sharia Bank has also implemented three layers of risk management defense, namely the First, Second and Third Lines of Defense, each of which is responsible for risk management at various levels.